44.7k views
4 votes
Consider the chemical equations shown here.

2NO2(g) ----> 2NO(g) + O2(g)

2NO(g) -----> N2(g) + O2(g)

N2(g) + 2O(g) ----> N2O4(G)


What is the equation for the overall reaction obtained by adding these equations?


2NO2(G) ----> N2O4(g)


2N204(g) + 2NO(g) ----> 2NO2(g) + 02(g)


N2 + O2(g) + 2NO(g) ----> N2O4 (g)

The answer is A

User ApenasVB
by
5.0k points

2 Answers

2 votes

Answer:

A.)

Step-by-step explanation:

Consider the chemical equations shown here. 2NO2(g) ----> 2NO(g) + O2(g) 2NO(g-example-1
User Sighingnow
by
5.0k points
3 votes

Answer: Chemical equation for the overall reaction obtained by adding these three given equations is:


2NO_2(g)\rightarrow N_2O_4(g)

Step-by-step explanation:


2NO_2(g)\rightarrow2NO(g)+O_2(g)...(1)


2NO(g)\rightarrow N_2(g)+O_2(g)...(2)


N_2(g)+2O_2(g)\rightarrow N_2O_4(g)...(3)

If the same compounds is on same sides in the reactions then add them.

If the same compound is on different sides of the reaction then subtract.

Adding (1) and (2)


2NO_2(g)+2NO(g)\rightarrow 2NO(g)+O_2(g)+N_2(g)+O_2(g)

NO is present on both sides, which means it will get cancel out.
O_2 is on same side it will get added up.


2NO_2(g)\rightarrow N_2(g)+2O_2(g)..(4)

Similarly, on adding (3) in (4) we get:


2NO_2(g)\rightarrow N_2O_4(g)

Above equation is obtained by adding given three equations.

User Mickie
by
4.7k points